Influence of pH Modification on Catalytic Activities of Metal-Doped IrO(2) Nanoparticles - Kim, Joo Yeon (Sci Rep, 2019)
The effects of pH variation on the catalytic activity of IrO(2) nanoparticles (NPs) doped with Cr (an early transition metal) or Ni (a late transition metal) depending on the amount of defect structures on the NP surfaces were analyzed. It was found that both Cr@IrO(2) and Ni@IrO(2) NPs, fabricated under basic conditions (pH = 13.5) denoted as Cr@IrO(2)-B and Ni@IrO(2)-B, respectively, were the best catalysts among the eight tested ones. Moreover, it was confirmed that variation in pH resulted in the changes in the surface area (defect structure), which were considered to be responsible for the changes in the catalytic properties of these NPs. For the oxygen evolution reaction, these NPs exhibited relatively smaller overpotential (η) values than other tested Cr@IrO(2)- and Ni@IrO(2)-containing NPs. Furthermore, methylene blue degradation analysis and OH radical formation experiments by benzoic acid showed the same trend. Thus, we confirmed that the catalytic activity of transition metals doped IrO(2) NPs fabricated under basic conditions can be improved.